DEVELOPING LEARNER-ORIENTED ENGLISH FOR NURSING SYLLABUS - Jacquelinda Sandra Sembel (Universitas Pelita Harapan, 2018)
English has become an inseparable part of Nursing career in non-English speaking countries, including Indonesia. At Universitas Pelita Harapan, student nurses need to take English for Nursing class to prepare them to communicate in English with overseas patients during their internship year. Goal: To identify these basic communication needs to use English at the hospital setting, Faculty of Nursing at Universitas Pelita Harapan developed mapping for English for Nursing syllabus and materials for the internship students. Methodology: A simplified research and development study was conducted to identify needs and to design and develop the appropriate English for Nursing Syllabus and materials. The study involved 33 nurses and 72 student nurses, covering needs analysis stage to syllabus mapping. Results: The result suggested that the course cover 10 communication topics from patient admittance to patient discharge over 16 sessions.